Study on Millimeter-Wave Vivaldi Rectenna and Arrays with High Conversion Efficiency - Guan-Nan Tan; Xue-Xia Yang; Huan Mei; Zhong-Liang Lu (International Journal of Antennas and Propagation)
A novel Vivaldi rectenna operated at 35 GHz with high millimeter wave to direct current (MMW-to-DC) conversion efficiency is presented and the arrays are investigated. The measured conversion efficiency is 51.6% at 35 GHz and the efficiency higher than 30% is from 33.2 GHz to 36.6 GHz when the input MMW power is 79.4 mW. The receiving Vivaldi antenna loaded with metamaterial units has a high gain of 10.4 dBi at 35 GHz. A SIW- (substrate integrated waveguide-) to-microstrip transition is designed not only to integrate the antenna with the rectifying circuit directly but also to provide the DC bypass for the rectifying circuit. When the power density is 8.7 mW/cm2, the received MMW power of the antenna is 5.6 mW, and the maximum conversion efficiency of the rectenna element is 31.5%. The output DC voltage of the element is nearly the same as that of the parallel array and is about half of the series array. The DC power obtained by the 1 × 2 rectenna arrays is about two times as much as that of the element. The conversion efficiencies of the arrays are very close to that of the element. Large scale arrays could be expended for collecting more DC power.